ANALISIS DESAIN KONTEN INSTAGRAM SEBAGAI STRATEGI PROMOSI @dkv.budiluhur - Desia, Archita (Kartala, 2023)
Digital marketing is a type of marketing activity that expands and improves on conventional marketing techniques by utilizing the internet and information technology. Social media is now a highly common promotional tool since it is thought to be excellent at swiftly and extensively sharing information. Instagram is a popular social networking website. Using Instagram as the primary promotional platform with the account name @dkv.budiluhur, Budiluhur Visual Communication Design (DKV), a new study program inside the Budi Luhur University, aims to raise brand awareness using a variety of tactics and impactful visual approaches.Using a qualitative descriptive approach and dissecting Tom Lincy's design theory on five design principles, namely balance, contrast, and unity research, this study intends to delve deeper into the effectiveness and influence of visual elements exhibited in @dkv.budiluhur's Instagram content. Results showed that the vision, mission, and goals of the study program at the Faculty of Communication & Creative Design were fulfilled by the Instagram feed material for the event category @dkv.budiluhur. The content design event DKV Homecoming, which was uploaded on June 6 and has 17800 views, has received the most likes between July 2022 and July 2021. Data is generated by design analysis. First, the places with the most color combinations are those that are lively and informal. The illustrations used are psychedelic types, and both text to illustration ratios are 18%. No contrast in the graphic stands out more than the others, despite the fact that contrast text has passed WCAG 2.0 at numbers 4 and 6.07.